De la notion de guérilla à la notion de techno-guérilla - Évolution technologique et transformation des machines de guerres - Noyer, Jean-Max (Études internationales, 1990)
Discussion is centered mainly on the concept of techno-guerilla warfare within a European context. After first considering the concept of guerilla warfare, we outline the relationships linking these two concepts. We then move on to discuss certain theoretical points regarding the adoption of this new form of technological warfare, as well as the stakes and the difficulties involved in adopting such a form of defence.